Addressing the mental health needs of adolescents in South African communities: a protocol for a feasibility randomized controlled trial - Sorsdahl, K.; van der Westhuizen, C.; Neuman, M.; Weiss, H.A.; Myers-Franchi, Bronwyn (2021)
Background: Like many low- and middle-income countries, almost half of the proportion of the South African population is under the age of 25. Given the peak age of onset for most mental health problems is in adolescence, it is vital that adolescents have access to mental health counselling. There are several initiatives to increase access to mental health counselling in South Africa, primarily through the integration of counselling for common mental disorders (CMD) into primary health care services, but adolescents (15–18 years of age) generally do not utilize these services. To address this gap, we will undertake a study to explore the feasibility of conducting a trial of the effectiveness of a community-based mental health counselling intervention for adolescents at-risk for a CMD.